Large Under-Resourced ELT Classes: What do the Learners Expect? - Ghimire, Ramesh Prasad (Journal of NELTA Surkhet, 2015)
This research explores the learners’ expectations in a large under-resourced ELT classes in Nepalese context. The researcher used a set of questionnaire as a tool for data collection. The data were collected from a total of one hundred secondary level students at different government- aided schools in Kathmandu valley. The collected data were analyzed quantitatively and qualitatively. The overall findings of the survey revealed that the learners expect a wide variety of activities to be used in a large ELT classroom. Similarly, they highly emphasize the rapport with the teacher, and expect normal speed of speech from the teacher while teaching. The implication of these and many other findings is that large and under-resourced ELT classes in Nepalese context need special attention on the part of the teacher. As far as possible collaborative activities like group and pair works should be encouraged and the teacher must be active and dynamic in the classroom paying attention to all kinds of learners. Journal of NELTA Surkhet Vol.4 2014: 64-69